THE HISTORICAL GEOGRAPHY OF THE CITY OF KARSHI DURING THE MANGIT DYNASTY EXPLAINED BY FOREIGN TRAVELERS - Karimov Bahrom Djalolovich; Do‘stmurodov O‘lmas (Bright Mind Publishing, 2025)
In the second half of the 18th century until the 1920s, during the period of the Mangit dynasty, the relations of the Bukhara Emirate with the neighboring countries were significantly developed. The geographically convenient location of the city of Karshi and on an important trade route made it possible for the Emirate of Bukhara to have comprehensive relations with neighboring countries such as Afghanistan and Iran. At the same time, it should be noted that the economic, trade and cultural relations between the cities of Samarkand and Tashkent and the neighboring regions of the Fergana Valley are carried out through this city.
Keywords: Mangit, Saklov gate, Chorsu, Registan, Sardoba Dome, verst, «Kalandarkhona», Kerki, Bukhoro gate, Amir Temur gate.